2015
DOI: 10.1111/pan.12616
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the 95% effective dose of remifentanil for the prevention of coughing during extubation in children undergoing tonsillectomy (with or without adenoidectomy)

Abstract: The ED95 of the continuous remifentanil infusion rate was 0.060 μg·kg(-1) ·min(-1) to prevent the cough response during extubation in children after tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…However, following a positive response (success of LOC), the next patient is randomized with a probability of 0.05 to the next lower dose and with a probability of 0.95 to the same dose. Examples of the biased coin up-and-down method in anesthesia studies finding an ED 95 dose can be found in numerous studies [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…However, following a positive response (success of LOC), the next patient is randomized with a probability of 0.05 to the next lower dose and with a probability of 0.95 to the same dose. Examples of the biased coin up-and-down method in anesthesia studies finding an ED 95 dose can be found in numerous studies [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the sample size for the Dixon's up‐and‐down sequential method has not been clearly defined; however, anaesthesia trials using the up‐and‐down method typically have 20–40 patients 14 . Based on the previous experience with this statistical method, a sample size of 80 paediatric patients was determined to generate a randomization list in a 1:1 ratio 15,16 …”
Section: Methodsmentioning
confidence: 99%
“…Examples of BCD in anesthesia studies include identifying the minimum effective dose of lidocaine or ropivacaine needed to effectively block the femoral nerve in 90% of subjects. Pediatric anesthesia examples include determining the speed of a propofol bolus at induction preserving respiration , finding an ED 95 dose of remifentanil allowing extubation without coughing post tonsillectomy , or determining the effect of obesity on ED 95 for propofol during induction .…”
Section: Sequential Design Methodsmentioning
confidence: 99%